SISTEM CYBER SECURITY DAN PENGAMANAN FILE PADA PENGAMANAN OBJEK VITAL PT TELKOM INDONESIA (PERSERO) Tbk - Edy Soesanto; Donni Ferdinan Irawan; Damar Asmarani; Putri Octavia Maharani (Cross-border, 2023)
This study discusses the cyber security system and file security in securing vital objects of PT Telkom Indonesia (Persero) Tbk. In the context of a critical telecommunications company, maintaining the security and confidentiality of vital objects and information stored in files is critical. This study identifies security measures that are generally implemented by PT Telkom Indonesia (Persero) Tbk in protecting vital objects and files containing important information. These measures include the use of firewalls, intrusion detection, protection against DoS attacks, data encryption, user identification and authentication, and continuous security monitoring. In addition, this research also provides suggestions for improving the cyber security system and file security of PT Telkom Indonesia (Persero) Tbk. These suggestions include increasing security awareness, regular security audits, collaboration with external parties, enhanced security monitoring, and research and innovation in cybersecurity. By implementing these steps and suggestions, PT Telkom Indonesia (Persero) Tbk can improve cyber security and file security on their vital objects, so as to protect information that is very important for the company and their customers.